Immunohistochemical Expression of IDH Mutation in Primary Brain Tumors: Ekspresi Imunohistokimia Mutasi IDH pada Tumor Otak Primer - Salim Mohammed, Amina; Al-Nuaimi, Hatem Abdulmajeed (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Brain tumors constitute 1–2% of adult tumors, with glioblastoma (GBM) and meningioma being the most frequent subtypes. Mutations in the isocitrate dehydrogenase (IDH) gene are associated with gliomas and have prognostic significance. Specific Background: Although IDH mutation is well-documented in secondary glioblastoma and diffuse gliomas, data remain scarce in Iraqi populations. Knowledge Gap: Limited studies exist on the prevalence and diagnostic role of IDH mutations in primary brain tumors in Mosul, Iraq. Aim: This study investigates the frequency, histopathological characteristics, and immunohistochemical expression of IDH mutations in primary brain tumors. Results: Among 41 cases (mean age 36.6 years), GBM (26.8%) and meningioma (22%) were predominant. Supratentorial tumors accounted for 75.6%. IDH immunohistochemistry in 10 cases revealed four positive results: medulloblastoma (25%), GBM (50%), atypical meningioma (100%), and gliosarcoma (100%). Meningioma grade I and anaplastic astrocytoma showed negative IDH expression. Novelty: This is the first documented case series in Mosul to highlight IDH expression patterns across multiple tumor subtypes, including rare positivity in atypical meningioma and gliosarcoma. Implications: Findings underscore IDH testing as a valuable diagnostic tool, supporting future integration into local neuropathological practice. Highlights: IDH mutation detected in multiple tumor subtypes. GBM was the most frequent brain tumor. Diagnostic role of IDH confirmed in local population. Keywords: Glioblastoma, IDH Mutation, Gliosarcoma, Isocitrate Dehydrogenase, Brain Tumors